Clinical usefulness of an ultra-high-sensitivity hepatitis B surface antigen assay to determine the cessation of treatment for HBV reactivation - Takanori Suzuki; Akihiro Tamori; Kentaro Matsuura; Takako Inoue; Shigeru Kusumoto; Shinya Hagiwara; Haruka Sagi; Atsushi Kaneko; Shuko Murakami; Hayato Kawamra; Kei Fujiwara; Katsumi Aoyagi; et al. (Annals of Hepatology)
Introduction and Objectives: We aimed to compare the usefulness of the ultra-high-sensitivity hepatitis B surface antigen (iTACT-HBsAg), high-sensitivity hepatitis B core-related antigen (iTACT-HBcrAg), and anti-HBs assays in determination of cessation of nucleot(s)ide analogue (NA) treatment to prevent against hepatitis B virus (HBV) reactivation. Patients and Methods: Twenty-two patients who developed HBV reactivation under immunosuppressive therapy or chemotherapy and had been administered NA and subsequently discontinued were enrolled. The stored serum samples taken at NA cessation were applied to iTACT-HBsAg (lower limit of detection; 0.0005 IU/mL), iTACT-HBcrAg (lower limit of detection; 2.1 log U/mL), and anti-HBs assays. Detection of serum HBV DNA level ≥1.3 log IU/mL after NA cessation was defined as virological relapse (VR). Results: Two patients were excluded due to re-introduction of NA despite a negligible level of HBV DNA (<1.3 log IU/mL). Of the remaining 20 patients, 11 (55 %) had HBcrAg <2.1 log U/mL at the cessation of NA, and 7 of the 11 patients (64 %) had no VR thereafter. On the other hand, 15 patients (75 %) had HBsAg <0.0005 IU/mL at the cessation of NA, and 13 of the 15 patients (87 %) subsequently lacked VR. Further, 12 patients (60 %) had anti-HBs ≥10 mIU/mL at the cessation of NA, and 10 of the 12 patients (83 %) had no VR thereafter. The iTACT-HBsAg assay had the highest positive predictive value and the best overall diagnostic performance for predicting non-VR after cessation of NA. Conclusions: The iTACT-HBsAg assay was useful to determine the cessation of NA treatment to prevent against HBV reactivation.